Donanemab Population Pharmacokinetics, Amyloid Plaque Reduction, and Safety in Participants with Alzheimer's Disease - Gueorguieva, Ivelina; Willis, Brian A.; Chua, Laiyi; Chow, Kay; Ernest, C. Steven; Shcherbinin, Sergey; Ardayfio, Paul; Mullins, Garrett R.; Sims, John R. (Clinical pharmacology and therapeutics, 2023)
Donanemab is an amyloid‐targeting therapy that resulted in robust amyloid plaque reduction and slowed Alzheimer's disease (AD) progression compared with placebo in the phase II TRAILBLAZER‐ALZ study (NCT03367403). The objectives of the current analyses are to characterize (i) the population pharmacokinetics of donanemab, (ii) the relationship between donanemab exposure and amyloid plaque reduction (response), and (iii) the relationship between donanemab exposure and amyloid‐related imaging abnormalities with edema or effusions (ARIA‐E). Model development included data from participants with mild cognitive impairment or mild to moderate dementia due to AD from the phase Ib study on donanemab (NCT02624778) and participants with early symptomatic AD from the TRAILBLAZER‐ALZ study. The analysis showed donanemab has a terminal elimination half‐life of 11.8 days. Body weight and antidrug antibody titer impact donanemab exposure but not the pharmacodynamic response. Maintaining a donanemab serum concentration above 4.43 μg/mL (95% confidence interval: 0.956, 10.4) is associated with amyloid plaque reduction. The time to achieve amyloid plaque clearance (amyloid plaque level < 24.1 Centiloids) varied depending on the baseline amyloid level, where higher baseline levels were associated with fewer participants achieving amyloid clearance. The majority of participants achieved amyloid clearance by 52 weeks on treatment. Apolipoprotein ε4 carriers, irrespective of donanemab serum exposure, were 4 times more likely than noncarriers to have an ARIA‐E event by 24 weeks.